The World of the Adams chronicles : forging our nation - Rothman, David J. (Boston : Educational Associates, 1976)
Presents contemporary writings from 1758-1893 which pertain to particular aspects of American history.
"A thirteen-week television series produced by WNET/13, New York, for national distribution by the Public Broadcasting Service."
Keywords: United States -- History; United States -- History -- Sources; United States -- History -- Sources